V type high birefringent PCF fiber for hydrostatic pressure sensing - Wójcik, Jan; Mergo, Pawel; Makara, Mariusz; Poturaj, Krzysztof; Skorupski, Krzysztof; Klimek, Jacek (Photonics Letters of Poland, 2010)
In the paper a new kind of optical fibres design for application in phase pressure sensors is presented. Fibres were modeled, fabrication technology was developed and the properties of fabricated fibres were measured. The results do not quite agree with those of modeling carried out by using commercially available software.